Mapping knowledge structure and emerging trends of extracorporeal membrane oxygenation for acute respiratory distress syndrome: a bibliometric and visualized study - Lu, Yanqiu; Li, Wanqing; Qi, Shaoyan; Cheng, Kunming; Wu, Haiyang (Frontiers in Medicine, 2024)
With the discovery of extracorporeal membrane oxygenation (ECMO), it is considered as a valuable tool for supporting the treatment of severe acute respiratory distress syndrome (ARDS). It has gained increasing attention, particularly during the COVID-19 epidemic. However, to date, no relevant bibliometric research on the association between ECMO and ARDS (ECMO-ARDS) has been reported. Our study aimed to summarize the knowledge structure and research focus of ECMO-ARDS through a bibliometric analysis.Method: Publications related to ECMO-ARDS from 2000 to 2022 were obtained from the Web of Science Core Collection (WoSCC). Research data underwent bibliometric and visual analysis by using CiteSpace, VOSviewer, and one online analysis platform.By analyzing the countries, institutions, journals, authors, the geographic distribution of research contributions as well as the leading institutions and researchers in this field were identified. Additionally, prominent journals and highly cited publications were highlighted, indicating their influence and significance in the field. Moreover, the cocitation references and co-occurring keywords provided valuable information on the major research topics, trends, and potential emerging frontiers.Results: A total of 1565 publications from 60 countries/regions were retrieved. The annual publication number over time revealed exponential growth trends (R 2 =0.9511).The United States was dominant in ECMO-ARDS research, whereas the Univ Toronto was most productive institution. Prof Combes A published the most publications in this area. ASAIO Journal and Intensive Care Medicine were the most active and co-cited journals, respectively. Reference co-citation analysis showed that current research focus has shifted to COVID-related ARDS, multi-center studies, as well as prone positioning.